PERANCANGAN STANDARD OPERATING PROCEDURE (SOP) PADA CHOCOLAB - Sheila Vania Winata (Universitas Ciputra Surabaya, 2016)
Chocolab is a food and beverage company which produces homemade chocolate. One of Chocolab's selling methods is consignment sales system through retailers. Sometimes, products are returned by retailers due to product defects caused by either the company or external parties. Since Chocolab does not have a Standard Operating Procedure (SOP), the quality of the product is not well-controlled. The purpose of this research is to design a good SOP for Chocolab's production and distribution processes. It is hoped that the SOP will lead to fewer product defects and more profit. This research is a qualitative explorative research which aims to obtain an in-depth comprehension by conducting an investigation on the selected informants. Purposive sampling is used to select the informants based on the criteria related to the research problems. The five study informants are three informants from other chocolate manufacturers, one logistic staff, and one chef. Interview, observation, and documentation are used as data collection methods in this research. The outcomes of this study include the SOP designs for raw material criteria and storage, production, product packaging and storage, and distribution.